Contribution Percentage Of Some Visual Functions and The Accuracy of Forehand Shot In Table Tennis - Abdul Amir, Haider (Journal of Physical Education, 2017)
The problem of the research lies in the weakness of table tennis athletes due tolack of performance accuracy. The importance of the research lies in finding a relationshipbetween the variables and finding a contribution percentage between visual functions and themost used shot in table tennis. The researcher used the deceptive method. The subjects were(8) advance table tennis athletes. The data was collected and treated using proper statisticaloperations. The researcher concluded a significant correlation relationship as well as contribution percentage between visual functions and the accuracy of shooting in tabletennis. Finally the researcher recommended the necessity of paying attention to visualfunctions on other sports and other subjects.